LRG1 promotes corneal angiogenesis and lymphangiogenesis in a corneal alkali burn mouse model - Song, Shan (Int J Ophthalmol, 2020)
AIM: To investigate the potential effect and mechanism of leucine-rich α-2-glycoprotein-1 (LRG1) on corneal angiogenesis and lymphangiogenesis. METHODS: Corneal neovascularization and lymphatics were induced by establishing alkali burn mouse model. Immunofluorescence staining was performed to detect the location of LRG1 in cornea tissues and to verify the source of LRG1-positive cells. Corneal whole-mount staining for CD31 (a panendothelial cell marker) and lymphatic endothelial hyluronan receptor-1 (LYVE-1; lymphatic marker) was performed to detect the growth of blood and lymphatic vessels after local application of exogenous LRG1 protein or LRG1 siRNA. In addition, expressions of the proangiogenic vascular endothelial growth factor (VEGF) related proteins were detected using Western blot analysis. RESULTS: LRG1 was dramatically increased in alkali burned corneal stroma in both the limbal and central areas. LRG1-positive cells in the corneal stroma were mainly derived from Vimentin-positive cells. Local application of exogenous LRG1 protein not only aggravated angiogenesis but also lymphangiogenesis significantly (P<0.01). LRG1 group upregulated the levels of VEGF and the vascular endothelial growth factor receptor (VEGFR) family when compared with the phosphate-buffered saline (PBS) control group. We also found that LRG1-specific siRNA could suppress corneal angiogenesis and lymphangiogenesis when compared with the scramble siRNA-treated group (P<0.01). CONCLUSION: LRG1 can facilitate corneal angiogenesis and lymphangiogenesis through heightening the stromal expression of VEGF-A, B, C, D and VEGFR-1, 2, 3; LRG1-specific siRNA can suppress corneal angiogenesis and lymphangiogenesis in corneal alkali burn mice.